Visualisasi Motif Batu Berelief Pada Karya Kayu Dua Dimensi - Rajum putra; Wisnu Prastawa (Penerbit dan Percetakan, CV. Picmotiv, 2025)
This work raises the shape of the relief stone motif as an idea for creating woodwork, the object of the shape of the relief stone motif raised by the creator of the shape of the motif on the stone. where this relief stone is used as a cultural heritage and the stone has been protected by the local community from the past until now because of the shape of the relief stone motif and its interesting texture, to be used as an idea for creating woodwork, the meaning and philosophy of the relief stone as the basis for the concept that will be realized in the creation. The process of creating this work through a three-stage method consisting of exploration, design, and embodiment. Exploration is to observe the shape of the relief stone motif. The design stage is the stage of applying ideas or ideas that are poured into alternative sketches and then become selected designs which will then be realized into works. The last stage is the embodiment of the work starting from the design. The embodiment uses surian wood material, with a middle or medium relief carving technique (mezzo relief), and finishing is done using print ink, which is coated using Clear Doft as a color cover when finishing the work, so that the color on the work is more durable and long lasting. The work consists of seven works which function as wall decorations.